Impacts of Cigarette Smoking Status on Metabolomic and Gut Microbiota Profile in Male Patients With Coronary Artery Disease: A Multi-Omics Study - Hu, Xiaomin; Fan, Yue; Li, Hanyu; Zhou, Ruilin; Zhao, Xinyue; Sun, Yueshen; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2021)
Background: Cigarette smoking has been considered as a modifiable risk factor for coronary artery disease (CAD). Changes of gut microbiota and microbe-derived metabolites have been shown to influence the atherosclerotic pathogenesis. However, the effect of cigarette smoking on gut microbiome and serum metabolites in CAD remains unclear. Method: We profiled the gut microbiota and serum metabolites of 113 male participants with diagnosed CAD including 46 current smokers, 34 former smokers and 33 never smokers by 16S rRNA gene sequencing and untargeted metabolomics study. A follow-up study was conducted. PICRUSt2 was used for metagenomic functional prediction of important bacterial taxa. Results: In analysis of microbial composition, the current smokers were characterized with depleted Bifidobacterium catenulatum, Akkermansia muciniphila and enriched Enterococcus faecium, Haemophilus parainfluenzae compared with the former and never smokers. In the untargeted serum metabolomic study, we observed and annotated 304 discriminant metabolites, uniquely including ceramides, acyl carnitines and glycerophospholipids. Pathway analysis revealed a significantly changed sphingolipids metabolism affected by cigarette smoking. While performing PICRUSt2 metagenomic prediction, several key enzymes (wbpA, nadM) were identified to possibly explain the crosstalk between gut microbiota and metabolomic changes associated with smoking. Moreover, the multi-omics analysis revealed that specific changes in bacterial taxa were associated with disease severity or outcomes by mediating metabolites such as fatty acid esters and glycerophospholipids. Conclusions: Our results indicated that both the gut microbiota composition and metabolomic profile of current smokers are different from that of never smokers. The present study may provide new insights into understanding the heterogenic influences of cigarette smoking on atherosclerotic pathogenesis by modulating gut microbiota as well as circulating metabolites.